Exploring The Faculty and Students’ Readiness Level for The Effective Implementation of Physical Activity Toward Health and Fitness Courses (PATHFIT) - Pineda, Herman S.; Andal, Edilberto Z.; Hermosa, Jherwin P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
he study aimed to evaluate students' preparation for physical activity in health and fitness courses at Laguna State Polytechnic University (LSPU) campuses. A descriptive correlational methodology was used in the study, which included 920 students and 48 faculty members. The findings demonstrate that PATHFIT courses are generally and substantially prepared at all LSPU campuses. The range of mean scores for each indicator demonstrates a high level of readiness, and given the modest standard deviation, readiness levels across several campuses may be constant. The courses specifically show how to prepare for streamlining curricular materials, objectives, methods, staffing policies, workforce management, alternative programs, physical education curriculum, laboratories, and equipment. These places a strong basis and foundation for the implementation of PATHFIT courses and are much ready. ANOVA results for the PATHFIT course implementation level throughout LSPU campuses, regarding the availability of facilities and resources, faculty qualification, and support system, revealed PATHFIT course implementation levels varied significantly among LSPU campuses. However, no appreciable differences across LSPU campuses' implementation levels of PATHFIT courses regarding the availability of facilities and resources and evaluation and monitoring attributable to the between-groups variation. In summary, regression analysis shows there are no appreciable differences between campuses regarding achieving goals and objectives, assessment and monitoring, or overall implementation level, and there are appreciable variations in the availability of facilities and resources, faculty credentials, and support systems. These results show how PATHFIT courses must be implemented consistently and successfully throughout LSPU to solve the inequalities in resources and qualifications between campuses. The study recommends ongoing promotion and improvement of health and fitness programs at LSPU campuses, as well as targeted interventions to enhance preparation levels and foster a culture of physical activity. Future research can explore innovative strategies to support a physically active lifestyle and contribute to overall well-being within the university community.